STUDY OF CAPITAL STRUCTURE AND PECKING ORDER DIMENSION AND SHAREHOLDERS' INTEREST IN MEDIA INDUSTRY - A COMPARATIVE STUDY OF ZEE TV AND NDTV - Sandeep Goel (Abhigyan, 2011)
Media industry in India has undergone an experiential phase during the last decade. The changes were evident in their financing pattern as well. The present article is an attempt to analyze the financing structure of two leading units in the sector, viz. Zee TV and NDTV with regard to pecking order dimension. Also, Shareholders' Wealth Maximization aspect of ROE maximization and market performance have been discussed in detail using Du Pont Analysis and Beta analysis respectively. It is found that Zee is going for the pecking order dimension in its capital structure, whereas pecking order analysis fails in case of NDTV. The impact of financial leverage on shareholders' return is more in case of NDTV, verified by high risk-high return, than in Zee TV.